Panorama mundial de las energías renovables e importancia de la energía solar fotovoltaica - Ballesteros-Ballesteros, Vladimir (Revista Científica, 2016)
This work presents a global panorama of the current state of consumption of renewable and fossil fuels in the world, paying special attention to photovoltaic solar energy and the need to formulate educational models and technological developments.